Potentially inappropriate medications prescribed for older persons: A study from two teaching hospitals in Southern India - Arun N Bhatt; Sherin S Paul; Smitha Krishnamoorthy; Basil T Baby; Anna Mathew; Balakrishnan R Nair (Journal of Family and Community Medicine, 2019)
BACKGROUND: Potentially inappropriate medications (PIMs) are a major concern in geriatric care. The primary objective of our study was to assess the prevalence of PIMs prescribed for older persons attending outpatient setting of two teaching hospitals in Kerala state in South India, where the population is aging. MATERIALS AND METHODS: A cross-sectional study was carried out in two teaching hospitals in Kerala. Four hundred consecutive outpatient medical records of patients aged 65 years and above were selected. The current medications of the patients were analyzed to identify PIMs by the Beers criteria 2015. Polypharmacy and hyperpolypharmacy were defined as 5–9 medications and ≥10 medications, respectively. Chi-square test was done to identify demographic variables and the pattern of health-care facility use associated with PIM prescription. Binary logistic regression was performed to adjust for confounding associations. RESULTS: The prevalence of PIMs prescription was 34.0% (95% confidence interval: 29.4%–38.6%) and that of polypharmacy and hyperpolypharmacy was 45.8% and 13.5%, respectively. The common PIMs were proton-pump inhibitors, benzodiazepines, peripheral α-1 blockers, and first-generation antihistamines. Inpatient admission, visits to the emergency department, multiple diagnoses, polypharmacy, and hyperpolypharmacy were associated with PIM prescription (P < 0.05). Age, gender, number of outpatient visits, and specialist consultation were not associated with PIM prescription. Polypharmacy (adjusted odds ratio [aOR] =2.11) and hyperpolypharmacy (aOR = 5.55) had independent association with PIM prescription (P < 0.05). CONCLUSION: PIM prescription appears to be common in teaching hospitals in Kerala. Polypharmacy and hyperpolypharmacy in older people should trigger a review of medication to reduce the use of PIM.